Yakov Syrkin: On the 125th anniversary of his birthday - S. S. Plotkin; A. V. Dorokhov; V. R. Flid (Тонкие химические технологии, 2019)
The article is dedicated to the 125th birthday of Yakov Kivovich Syrkin - Academician, Doctor of Chemical Sciences, Professor, Laureate of the Stalin Prize, and founder of the school of quantum chemistry in Russia. He was the head of the departments of Physical Chemistry at the M. V. Lomonosov Moscow Institute of Fine Chemical Technology and of Simple and Complex Compounds at the N.S. Kurnakov Institute of General and Inorganic Chemistry of the USSR Academy of Sciences, and the Laboratory of the Structure of Molecules at the L.Ya. Karpov Institute of Physical Chemistry. Yakov Syrkin was a world-famous scientist in the field of physical chemistry, who has addressed many issues of quantum chemistry, molecules structure, chemical bonds; the mechanism of chemical reactions, kinetics and catalysis. He was a brilliant teacher and lecturer, the initiator of many scientific ideas and directions, the author of more than five hundred scientific works, a responsive man of many talents. The chronological outline of his scientific, pedagogical and life path is presented, some less well-known fa.cts about his biography has also been highlighted.